2007
DOI: 10.1111/j.1365-2958.2007.06029.x
|View full text |Cite
|
Sign up to set email alerts
|

RsaL provides quorum sensing homeostasis and functions as a global regulator of gene expression in Pseudomonas aeruginosa

Abstract: SummaryThe quorum sensing (QS) signalling system of Pseudomonas aeruginosa controls many important functions, including virulence. Although the production of the QS signal molecule N-3-oxo-dodecanoylhomoserine lactone (3OC12-HSL) is positively autoregulated, its concentration reaches a steady level long before stationary phase. The RsaL protein represses transcription of the lasI signal synthase gene, and thus reduces QS signal production. We show that RsaL binds simultaneously with LasR to the rsaL-lasI bidir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
196
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(211 citation statements)
references
References 40 publications
(79 reference statements)
14
196
0
1
Order By: Relevance
“…QteE and QscR dampened the expression of QS target genes after transition to the 'on' state, providing homeostatic regulation. A similar mechanism balances 3OC12-HSL production in P. aeruginosa: RsaL, another QS repressor, is activated by LasR and directly represses lasI transcription (Rampioni et al, 2006;Rampioni et al, 2007). Thus, the initial positive feedback mechanism in QS, autoinduction, is tightly coupled with and immediately followed by multiple negative feedback mechanisms that confine the metabolic cost of public goods production.…”
Section: Discussionmentioning
confidence: 99%
“…QteE and QscR dampened the expression of QS target genes after transition to the 'on' state, providing homeostatic regulation. A similar mechanism balances 3OC12-HSL production in P. aeruginosa: RsaL, another QS repressor, is activated by LasR and directly represses lasI transcription (Rampioni et al, 2006;Rampioni et al, 2007). Thus, the initial positive feedback mechanism in QS, autoinduction, is tightly coupled with and immediately followed by multiple negative feedback mechanisms that confine the metabolic cost of public goods production.…”
Section: Discussionmentioning
confidence: 99%
“…The rsaL and lasI genes are divergently transcribed and coregulated. LasR binding to the lasI-rsaL intergenic region triggers transcription of both genes Schuster, 2004b), while RsaL binding results in repression of lasI-rsaL transcription (Rampioni, 2007), ensuring tight control of this negative regulator. Rampioni et al (2007) demonstrated that while RsaL and LasR are capable of binding simultaneously to the intergenic region; repression by RsaL supersedes LasR-mediated activation (Rampioni, 2007).…”
Section: Regulators Of Qs Homeostasismentioning
confidence: 99%
“…LasR binding to the lasI-rsaL intergenic region triggers transcription of both genes Schuster, 2004b), while RsaL binding results in repression of lasI-rsaL transcription (Rampioni, 2007), ensuring tight control of this negative regulator. Rampioni et al (2007) demonstrated that while RsaL and LasR are capable of binding simultaneously to the intergenic region; repression by RsaL supersedes LasR-mediated activation (Rampioni, 2007). RsaL appears to be a global regulator, controlling ~130 genes independent of its effect on lasI expression (Rampioni, 2007), including genes whose products are involved in antibiotic resistance and biofilm formation in P. aeruginosa (Rampioni, 2009).…”
Section: Regulators Of Qs Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome analysis indicates that Vfr affects the expression of more than 100 genes in P. aeruginosa including T3SS genes (29). RsaL (PA1431), which is divergently transcribed from the lasI gene, encodes an autoregulating repressor that inhibits not only lasI transcription, but also genes involved in pyocyanin and cyanide synthesis (372,373). Interestingly, RsaL repression is dominant over 3-oxo-C12-HSL:LasR activation of lasI to counteract the positive feedback loop (372).…”
Section: Quorum Sensing (Qs)mentioning
confidence: 99%